NOVEL PREDICTORS OF PERITONITIS-RELATED OUTCOMES IN THE BRAZPD COHORT - Proenca de Moraes, Thyago; Olandoski, Marcia; Caramori, Jaqueline C. T. [UNESP]; Martin, Luis Cuadrado [UNESP]; Fernandes, Natalia; Carolino Divino-Filho, Jose; Pecoits-Filho, Roberto; Barretti, Pasqual [UNESP]; BRAZPD Study Grp (Multimed Inc, 2014)
Introduction: Peritonitis remains the main cause of peritoneal dialysis (PD) technique failure worldwide, despite significant reductions in infection rates observed over the past decades. Several studies have described risk factors for peritonitis, technique failure and mortality. However, there are scarce data regarding predictors of complications during and after a peritonitis episode. The aim of our study was to analyze predictors of peritonitis-related outcome in the Brazilian Peritoneal Dialysis study (BRAZPD) cohort.Methods: All adult incident patients recruited in the BRAZPD Study between December 2004 and October 2007, who remained at least 90 days on PD and presented their first peritonitis episode (n = 474 patients) were included in the study. The endpoints analyzed were non-resolution, death due to a peritonitis episode and long-term technique survival after a peritonitis episode.Results: In the multivariable regression, non-resolution was independently associated with older age (odds ratio (OR) 1.02; p < 0.01), collagenosis as the primary renal disease (OR 4.6; p < 0.05) and Pseudomonas spp as etiological agent (OR 2.9; p < 0.05). Patients who were transferred from APD to CAPD during peritonitis therapy presented a higher risk of non-response (OR 2.5; p < 0.05). The only factor associated with death during a peritonitis episode was older age (OR 1.04; p < 0.05). Exposure to vancomycin and male gender were the independent predictors of long-term technique failure (OR 2.2; p < 0.01).Conclusion: Apart from confirming previous observations of the negative impact of older age and Pseudomonas spp peritonitis on outcomes, we observed that collagenosis may negatively impact response to treatment and exposure to vancomycin may possibly reduce long-term technique survival. It is important to emphasize that the association of vancomycin with technique failure does not prove causality. These findings shed light on new factors predicting outcome when peritonitis is diagnosed.
Keywords: Peritoneal dialysis; peritonitis; BRAZPD; clinical outcomes